FRI0070 Angiotensin II type 2 receptor (AT2R) is overexpressed in rheumatoid arthritis and osteoarthritis synovium and increases steadily with inflammatory stimuli: a potential new target for pain and anti-inflammatory therapies. (15th June 2017) - Terenzi, R; Manetti, M; Rosa, I; Romano, E; Galluccio, F; Guiducci, S; Ibba-Manneschi, L; Matucci-Cerinic, M
Abstract : Background: Despite increasing evidence suggesting that angiotensin II type 2 receptor (AT2R) antagonism might be a feasible strategy for the treatment of chronic inflammation and pain, no study has yet analyzed the synovial expression of AT2R. Objectives: To investigate the expression of AT2R in rheumatoid arthritis (RA) and osteoarthritis (OA) synovium and its possible modulation in fibroblast-like synoviocytes (FLS) by proinflammatory stimuli. Methods: The expression of AT2R in RA and OA synovium was investigated by immunohistochemistry. AT2R expression in synovial T cells, B cells, macrophages and FLS was assessed by double immunofluorescence. FLS were isolated from healthy (H), OA and RA synovium and treated with tumor necrosis factor (TNF)-α and interleukin (IL)-1β, alone or in combination. Immunocytochemistry and Western blotting were performed to study AT2R expression in cultured FLS. Results: RA synovium showed stronger AT2R immunostaining than OA synovium in the lining and sublining layers. In RA synovium, AT2R was strongly expressed in CD3+ T cells, CD20+ B cells, CD68+ macrophages and vimentin+ FLS. High levels of AT2R were found in OA-FLS and RA-FLS at baseline, while AT2R expression was negligible in basal H-FLS. AT2R expression was higher in RA-FLS than OA-FLS. Treatment with TNF-α and IL-1β was able to foster the expression of AT2R not only in OA-FLS and RA-FLS, but also in H-FLS. Conclusions: AT2R is strongly expressed in different cell types of the inflamed synovium and proinflammatory stimuli may foster the expression of AT2R in FLS. AT2R might represent a novel potential therapeutic target in chronic arthritides. Disclosure of Interest: None declared